(untitled) (Journal of the College of Education for Women, 2019)
To learn about the importance of ethics in different historical eras have to be identified first on the roots of this concept and return to the origins of language and the statement connotations Home as a morality single won Position good in the literature of the Arabic language , and beliefs of the monotheistic religions that see the majority it had on moral grounds .The name of the morality of the natural qualities of a human being , or the name of human nature itself , and morality , plural ( created) is the name of the inner configuration of this man , but Valkhalq put against the word of creation - which is the name of this human form evolving .In the opinion of other references that word ( ethics ) but they are collecting for the word (create) and usually means the repetition of a certain act , man who create characterized the behavior of a constant in his daily life , but it is said that the word ( create ) is taken from the word ( succession ) meaning " Exercise the thing even those who practiced becomes ahabit , "as some believe that the creation of the Queen of queens self- published by the actions of human or without careful thought or deliberately .There are those who believe that the word of creation comes the sense of conduct or behavior (behaviour), or in the sense of conduct and manners (manner, or in the sense of moral and ethical behavior (moral), or in the sense of moral lesson , or morality (morality), or in ethics they understood philosophically (ethics), or in the sense of ethical or moral (ethical).If the science of importance to the advancement of human and material civilization , the morals are more important to relate to aspect spiritual in humans , is not seen by every human being to be a scientist or be mastered theories of science, but consider him to realize the meaning of ( duty ) , and aims at work and his actions to achieve ethical principles , so the issues that must be of interest to every man , being a need not to build his actions and justified by reference to the moral principle , and if you do not take his position on the ethical problems facing it and preferred to be negative , the negative be moral , so it should be every human being should take it as a principle and measures applied by his actions and by his actions and judged based on the actions of others and their actions.Therefore we can return to say that the subject ( ethics ) is acts humanity in terms of compliance with the good and evil and their relationship to duty and the ideal of behavior , the topics addressed by the ( ethics ) are basically good and evil , conscience, and the right and duty and the ideal and principles leading to human life -Semitism